URGENSI QASHAS AL-QURAN DALAM PEMBELAJARAN - Sidiq, Umar (IAIN Ponorogo, 2011)
Al-Qurâan Qashas is news of al-Qurâan about the state of the former peoples, the Prophet and the events that have occurred. It is generally asserted thatÂ theÂ stories in the Quran provide abundant benefits such as confirming the heart of god messenger, justifying the previous Prophets, uncover the lies of the scripture with hujjah, Â and the story is one of literary worksÂ that can attract the attention of listeners and explain the principles of dawah to Allah as well. It is undoubtedly that a well-organized story will be easily catching the listenersâ soul and people will be also fond of accepting it, even they will not get bored due to the essence of story. By reflecting the benefits of the story in Al-Qurâan, it is recommended that the educators should take its advantage during the learning process in the classroom, especially on Islamic learning lesson since this subject is regarded as fundamental and core of Islamic education objectives. Therefore, the stories in Quran play an important role as a fruitful media that can help teachers educate the students and achieve their instructional goals successfully.Â Â Â Â ÙØµØµ Ø§ÙÙØ±Ø£Ù ÙÙ Ø§Ø®Ø¨Ø§Ø±Ù Ø¹Ù Ø§ØÙØ§Ù Ø§ÙØ£Ù Ù Ø§ÙÙ Ø§Ø¶ÙØ©, ÙØ§ÙÙØ¨ÙØ§Øª Ø§ÙØ³Ø§Ø¨ÙØ©, ÙØ§ÙØÙØ§Ø¯Ø« Ø§ÙÙØ§ÙØ¹Ø©. ÙØ§ Ø´Ù ÙÙÙ Ø§Ù Ø§ÙÙØµØ© Ø§ÙÙ ØÙÙ Ø© Ø§ÙØ¯ÙÙÙØ© ØªØ·Ø±Ù Ø§ÙÙ Ø³Ø§Ù Ø¹ Ø¨Ø´ØºÙ- ÙØªÙÙØ° Ø§ÙÙ Ø§ÙÙÙØ³ Ø§ÙØ¨Ø´Ø±ÙØ© Ø¨Ø³ÙÙÙØ© ÙÙØ³Ø±, ÙØªØ³ØªØ±Ø³Ù Ù Ø¹ Ø³ÙØ§ÙÙØ§ Ø§ÙÙ Ø´Ø§Ø¹Ø± ÙÙØ§ ØªÙ Ù ÙÙØ§ ØªÙØ¯, ÙÙØ±ØªØ§Ø¯ Ø§ÙØ¹ÙÙ Ø¹ÙØ§ØµØ±ÙØ§ ÙÙØ¬ÙÙ Ù Ù ØÙÙÙÙØ§ Ø§ÙØ£Ø²Ø§ÙÙØ± ÙØ§ÙØ«Ù Ø§Ø±. ÙØ°Ù Ø§ÙØ¸Ø§ÙØ±Ø© Ø§ÙÙØ·Ø±ÙØ© Ø§ÙÙÙØ³ÙØ© ÙÙØ¨ØºÙ ÙÙÙ Ø±Ø¨ÙÙ Ø§Ù ÙÙÙØ¯ÙØ§ Ù ÙÙØ§ ÙÙ Ù Ø¬Ø§ÙØ§Ø© Ø§ÙØªØ¹ÙÙÙ , ÙØ§Ø³ÙÙ Ø§ Ø§ÙØªÙØ°ÙØ¨ Ø§ÙØ¯ÙÙÙ, Ø§ÙØ°Ù ÙÙ ÙØ¨ Ø§ÙØªØ¹ÙÙÙ , ÙÙÙØ§Ù Ø§ÙØªÙØ¬ÙÙ ÙÙÙ. ÙÙÙ Ø§ÙÙØµØµ Ø§ÙÙØ±Ø£Ù ØªØ±Ø¨Ø© Ø®ØµØ¨Ø© ØªØ³Ø§Ø¹Ø¯ Ø§ÙÙ Ø±Ø¨ÙÙ Ø¹ÙÙ Ø§ÙÙØ¬Ø§Ø ÙÙ Ù ÙÙ ØªÙÙ Ù ØªÙ Ø¯ÙÙ Ø¨Ø²Ø§Ø¯ ØªÙØ°ÙØ¨Ù.